Dokumentarische Methode: Triangulation und blinde Flecken - Olaf Dörner, Peter Loos, Burkhard Schäffer, Anne-Christin Schondelmayer (Verlag Barbara Budrich, 2019)
The volume discusses the possibilities and limits of the documentary method in terms of basic theory, methodology and methodology. Triangulation is important in two ways: as a research practice in itself and as a way of identifying blind spots. The interest in the topic of triangulation - taking on different perspectives - relates above all to questions about the possibilities and limits offered by the documentary method for triangulation in terms of basic theory, methodology, and method. This goes beyond the common understanding of triangulation as mixed methods, which involves the combination of different methods and the validation of results. The second part of the book deals with "blind spots" of the documentary method, which become clear in comparison with other methodologies and procedures of empirical social and educational research, but which are also constituted and revealed in the actual research practice (in the field of research). Both dimensions are taken into account in the volume.